Development and validation of an ultra-performance liquid chromatography mass spectrometry/mass spectrometry method for simultaneous quantification of total and free mycophenolic acid and its metabolites in human plasma - Napatsanan Tanathitiphuwarat; Pannee Tanudechpong; Pajaree Chariyavilaskul; Nantaporn Prompila; Nat Tansrisawad; Apinya Tubtimrattana; Supeecha Wittayalertpanya (Wolters Kluwer Medknow Publications, 2020)
A reliable method has been validated using ultra-performance liquid chromatography mass spectrometry (MS)/MS for simultaneous evaluation of human plasma concentration of mycophenolic acid (MPA) and its major metabolites both total and free form. All analytes were extracted from plasma by simple protein precipitation procedure with methanol. Samples for determination of their free form concentration require a preanalytic spin through an ultrafiltration system. The chromatographic separation was completed using C18column at 0.3 ml/min with a gradient condition. Method validation was performed as the United State Food and Drug Administration guidelines for bio-analytical methods concerning precision, accuracy, linearity, selectivity, recovery, and matrix effect. Linearity was obtained over concentration of 0.05-4, 0.5-60, and 0.025-3 μg/ml for total MPA, mycophenolic acid glucuronide (MPAG) and mycophenolic acid acyl-glucuronide (AcMPAG), respectively. The linearity of the method for free form of analytes was confirmed in the range of 10-500, 125-10,000, and 0.5-300 ng/ml for MPA, MPAG, and AcMPAG, respectively. The intra- and interday accuracy ranged from 85.73%-102.01% for total form, and 87.23%-111.89% for free form, and the precisions of all analytes were lower than 15%. The mean recoveries of the analytes ranged from 85.54% to 94.76% and the matrix factor ranged from 0.88-1.06. The developed method is rapid, sensitive and convenient for pharmacokinetic study or therapeutic drug monitoring in patients after oral administration of enteric-coated mycophenolate sodium or mycophenolate mofetil.